72. Impaired pain processing in patients with silent myocardial ischemia. Issue 1 (January 2015) - Vollono, C.; Di Franco, A.; Lanza, G.; Mazzucchi, E.; Russo, G.; Villano, A.; Virdis, D.; Pazzaglia, C.; Sestito, A.; Crea, F.; Rossini, P.M.; Valeriani, M.
<x xml:space="preserve">Abstract</x> The aim of the study was to investigate the nociceptive system in patients with silent Myocardial Ischemia (MI) by CO2 laser evoked potential (LEP) recording. We studied 3 groups: (1) 11 asymptomatic, non-diabetic patients with documented obstructive Coronary Artery Disease (CAD) (silent-MI group); (2) 10 patients with obstructive CAD showing the clinical pattern of chronic stable angina (symptomatic-MI group); (3) 14 healthy subjects matched for age and gender to patients (control group). LEPs were recorded from 3 electrodes, placed at Cz, Fz, and T3 according to 10–20 International System, in response to chest as well as right hand skin stimulation. Three sequences of stimuli were applied, separated by 5-min intervals. N2-P2 amplitude during the first sequence of chest stimulation was reduced in silent-MI group compared to other groups (p = 0.03). N2-P2 amplitude decreased across the three sequences of stimuli in symptomatic-MI group and control group, but not in silent-MI group (comparison among groups, p = 0.015). CAD patients with silent-MI show a reduced amplitude of N2–P2 component and inadequate habituation to painful stimuli. These findings are consistent with an abnormal central pain processing in patients with silent-MI that might, at least in part, explain their typical misperception.